Neutrophil Extracellular Traps Exacerbate Secondary Injury via Promoting Neuroinflammation and Blood–Spinal Cord Barrier Disruption in Spinal Cord Injury - Feng, Zhou; Min, Lingxia; Liang, Liang; Chen, Beike; Chen, Hui; Zhou, Yi; Deng, Weiwei; Liu, Hongliang; Hou, Jingming (Frontiers in Immunology, 2021)
As the first inflammatory cell recruited to the site of spinal cord injury (SCI), neutrophils were reported to be detrimental to SCI. But the precise mechanisms how neutrophils exacerbate SCI remain largely obscure. In the present study, we demonstrated that infiltrated neutrophils produce neutrophil extracellular traps (NETs), which subsequently promote neuroinflammation and blood-spinal cord barrier disruption to aggravate spinal cord edema and neuronal apoptosis following SCI in rats. Whereas, both inhibition of NETs formation by peptidylarginine deiminase 4 (PAD4) inhibitor and disruption of NETs by DNase 1 alleviate secondary damage, thus restraining scar formation and promoting functional recovery after SCI. Further, we found NETs exacerbate SCI partly via elevating transient receptor potential vanilloid type 4 (TRPV4) level in the injured spinal cord. Therefore, our results indicate that NETs might be a promising therapeutic target for SCI.